(untitled) (Journal of actual problems of jurisprudence, 2018)
The article analyzes the concept of clinical education and its application possibilities in this educational process. The history of the development of student legal clinics in the world and in Kazakhstan. We investigate concepts such as «objective clinical education», «methods of clinical education», «clinical education forms.» In the example of a student legal clinic analyzed the characteristics of this form of learning. Key words: law degree, student clinic, methods of clinical education, clinical forms of education.